Teaching Antonyms to Arabic-Speaking EFL Learners - Altakhaineh, Abdel Rahman Mitib; Hajjo, Maram H. (International journal of emerging technologies in learning, 2019)
This study investigates the impact of different teaching techniques, e.g. projecting pictures using an overhead projector and the traditional way of teaching, in improving Arabic-speaking EFL learners’ production of antonyms in English. A production test was administered, including 20 pairs of antonyms, to assess the students’ knowledge of English antonyms before the instructional intervention. To this end, 40 grade six students were divided into two groups: treatment and control. After the instructional intervention, a Pictionary Test was implemented, including 10 pairs of antonyms as post-test to determine if projecting pictures via an overhead projector can be an effective technique in increasing students’ production of English antonyms. The results showed that the number of accurate answers provided by the treatment group (who were taught using pictures via overhead projector) was higher than that provided by the control group (who were taught via the traditional method). This suggests that the former teaching technique may have played an important role in their performance on the test. It can be concluded that teaching via overhead projector with pictures seems to be an effective instructional intervention in teaching English antonyms.